An industrial quality control study on Splash Corporation - Argomido, Lanie (College of Engineering, 2004)
This paper is all about an Industrial Quality Control Study conducted on Splash Corporation. This study focused on one product, which is the Skin White Face Scrub since it is one of their newest products, which was introduced only last April 2003. The group conducted a series of plant visits to be able to document their existing systems and processes. Data gathering served as an essential part in these visits. From the data collected for the month of July, three main problems were recognized. These are low percent yield, low viscosity due to bubbly consistency and machine breakdown. Statistical Process Control tools and techniques were used to identify and analyze these problems. For problem identification, Pareto Chart, and Cause and Effect Diagram were used. It was found out that the problem of low percent yield could be addressed only after the problem with low viscosity is solved. According to the supervisor, the problem with machine breakdowns was mainly due to the inefficient preventive maintenance of these machines. Thus, the main problem addressed is low viscosity. To test whether the processes involved in producing the Skin White Face Scrub is in control, the group used control charting. The X chart and Moving Range (x-Rm) chart were used since the sample size is equal to one and the parameters involved can be considered as variable. The three parameters tested were viscosity, pH and specific gravity. The actual values for these three parameters showed out of control points. The control chart for pH produced the greatest number of out of control points. Assignable causes should first be determined and controlled before the process capability for the pH parameter to proceed. Although the parameters viscosity and specific gravity showed some out of control points, the charts were revised to make it in-control. After some points were eliminated, the process capabilities of the two parameters were computed. It showed that the process is not capable of producing a product within the specification limits of the viscosity but is capable of producing within the specification limit of specific gravity. The viscosity uses more than 100 percent of the specific band. From the results of the Statistical Process Control and Process Capability Analysis, it was found out that the compounding process involved in manufacturing of Skin White Face Scrub encounters a lot of variability. These variabilities should be reduced, if not eliminated. To do so, assignable causes should be determined but the records failed to give insights on these assignable causes. Thus, the group recommends that the company, first, improve their recording systems. Training of workers for the possible changes in recording system is important. In the long run, it is also advisable to come up with a compounding machine that has an automated recording system to keep information of the actual readings of these parameters. Additional forms like Corrective Action Form can be added in the Non-Conforming Material Report form to aide in the analysis of problems. Comprehensive recording system for machine breakdowns should also be implemented to help in preventive maintenance schedule. These are the recommendations that the group proposes to the company. Implementations of these are still under the management's approval. Also, some other factors not included in this study like cost analysis should be taken into account.